Endovascular Repair of Symptomatic Hemodialysis Access Graft Pseudoaneurysms. Issue 1 (January 2014) - Fotiadis, Nicos; Shawyer, Andrew; Namagondlu, Girish; Iyer, Arun; Matson, Matthew; Yaqoob, Muhammad Magdi
Aim: Repeated needle punctures of arteriovenous hemodialysis grafts can lead to the development of pseudoaneurysms. As they enlarge, graft pseudoaneurysms are associated with significant morbidity and require treatment. We present our single-center experience using stent grafts in selected patients to exclude symptomatic hemodialysis graft pseudoaneurysms. Materials and Methods: Between March 2007 and December 2010, 11 consecutive patients (7 men and 4 women, mean age 57 years) underwent percutaneous endovascular repair of symptomatic hemodialysis access graft pseudoaneurysms. Indications for treatment were rapidly enlarging pseudoaneurysm in 5 patients, high venous pressures, limb edema and pseudoaneurysm in 3, skin breakdown over the pseudoaneurysm site in 2 and acute rupture and bleeding in 1 patient. No patient was lost to follow-up. Results: Technical success across the 11 patients was 90.9%. The patient who presented with rupture required ligation of the access due to continuous bleeding after stent graft insertion. Balloon angioplasty of a separate hemodynamically significant stenosis at the time of stent graft insertion was performed in 7 of 11 (63.6%) patients. The primary access patency rates were 72.7% (95% CI of 0.390-0.939) at 3 months and 36.4% (95% CI 0.109-0.692) at 6 months. Secondary access patency rates were 72.7% at 6 months (95% CI 0.233-0.832). There were no procedure-related complications. Mean follow-up was 9 months (range 2-29 months). Conclusions: Endovascular treatment of symptomatic hemodialysis graft pseudoaneurysms is safe and effective with similar patency rates to surgical approaches. Importantly, this approach allows aggressive management of associated access circuit stenoses at the same time and avoids interval tunneled dialysis line insertion.